Microstructure and electrical properties of porous BZT-0.5BCT ceramics: Effect of pore formers (PVA and PVP). (10th September 2017) - Abhinay, S.; Bhukania, S.; Mazumder, R.
ABSTRACT: Porous ceramic was prepared by mixing BZT-0.5BCT with different percentage (10, 20, 30 and 40 vol%) of polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP) as pore-forming agents (PFA). Density, relative permittivity, remanent polarization and piezoelectric constant decreased linearly with increase in pore former addition. Pores derived from the pore former were spherical to irregular in shape. Isolated pores are observed with addition of PVA up to 20 vol% and pore interconnectivity is observed at 40 vol%. Incidentally pore interconnectivity is observed even at 20 vol% addition in case of PVP. The decrease in electrical properties is much higher in PVP when compared with PVA as a pore former.